Disaster justice for people with disabilities. Issue 2 (8th October 2020) - Ton, Khanh That; Adamson, Carole
Abstract : Purpose: The purpose of this article is to examine disaster justice for people with disabilities (PWD). Design/methodology/approach: Drawing on the capability approach, the article explores distributive injustice that PWD face in dealing with disasters. It discusses procedural justice with a focus on the agency of PWD and their participation in decision-making processes concerning disaster risk reduction. Findings: It argues that disaster injustice faced by PWD can be construed as the inequalities of capabilities that they experience in coping with disasters. Furthermore, although social structures play an important role in creating and perpetuating disaster injustice, PWD, as agents of change, have power to transform social structures that, in turn, bring about justice for themselves. Originality/value: The article raises the need for considering the equality of capabilities and human agency in achieving disaster justice for PWD.